The road to achieving epidemic-ready primary health care. (May 2023) - Frieden, Thomas R; Lee, Christopher T; Lamorde, Mohammed; Nielsen, Marci; McClelland, Amanda; Tangcharoensathien, Viroj
Summary: Millions of avoidable deaths arising from the COVID-19 pandemic emphasise the need for epidemic-ready primary health care aligned with public health to identify and stop outbreaks, maintain essential services during disruptions, strengthen population resilience, and ensure health worker and patient safety. The improvement in health security from epidemic-ready primary health care is a strong argument for increased political support and can expand primary health-care capacities to improve detection, vaccination, treatment, and coordination with public health—needs that became more apparent during the pandemic. Progress towards epidemic-ready primary health care is likely to be stepwise and incremental, advancing when opportunity arises based on explicit agreement on a core set of services, improved use of external and national funds, and payment based in large part on empanelment and capitation to improve outcomes and accountability, supplemented with funding for core staffing and infrastructure and well designed incentives for health improvement. Health-care worker and broader civil society advocacy, political consensus, and bolstering government legitimacy could promote strong primary health care. Epidemic-ready primary health-care infrastructure that is able to help prevent and withstand the next pandemic will require substantial financial and structural reforms and sustained political and financial commitment. Governments, advocates, and bilateral and multilateral agencies should seize this window of opportunity before it closes.